Infodemia, heranças intertextualizadas e simbioses: as “Inteligências Construídas” através da biobibliografia de Fábio Fernandes no romance Os Dias da Peste - Souto, Gabriela Barbosa de (2021)
The Cyberpunk Movement, heir to the New Wave of science fiction, emerges in the 1980s as a vanguard movement that breaks with the common place of the genre narratives produced until then. The punk attitude combined with its dystopian atmosphere and information technologies, inserted in a scenario dominated politically and economically by large corporations, was a great success, influencing narratives not only in literature, but also in cinema, television and videogames. If the relationship between men and machines has always found space in science fiction to be discussed, from cyberpunk onwards, this issue faces a favorable environment for ontological debates when exploring the most varied forms of life, highlighting androids and artificial intelligences. Cyberpunk as a literary subgenre arrived in Brazil almost a decade later, with the translations of Islands on the Net (STERLING, 1990) and Neuromancer (GIBSON, 1991). Brazilian cyberpunk, unlike Anglophone narratives, is full of particularities and, when reinterpreting the subgenre, it brings in its plots characteristics such as: the plurality of voices, socioeconomic inequalities, urban counterculture, mysticism and the emptying of technology, to name a few. Still in the 2000s, the journalist, professor, writer and translator Fábio Fernandes published his first novel, Os Dias da Peste. The narrative, structured in the form of a diary, recounts the awakening of the machines, which will come to be known as “Built Intelligences”, from the perspective of the computer technician and professor Artur Mattos. Despite this being a recurrent theme in the literary genre, Fernandes' novel (2009) becomes unique when it uses different timelines and media supports, while making use of numerous non-fiction references, building a metanarrative that also maps a part of science fiction history. If, a priori, the proposal of this thesis aimed to explore the relationship between human users and "Built Intelligences", thinking of these as artificial and autonomous life forms that refer to the problematics of the post-human, new analytical possibilities proved to be plausible from of intertextual references that escape the fictional domain. Based on the indicative paradigm (GINZBURG, 1989), this thesis also investigates the evidence left by Fábio Fernandes throughout the narrative of Os Dias da Peste, which indicate, through its structure and referentiality, both a mapping of the literary genre and the biobibliographic place of the author, thinking of him as an heir to the canonical tradition of science fiction, which escapes the genre from its unique context.